The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ma13051035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fly Ash Fractionation on the Zeolitization Process

Abstract: Coal combustion product in the form of fly ash has been sieved and successfully utilised as a main substrate and a carrier of silicon and aluminium in a set of hydrothermal syntheses of zeolites. The final product was abundant in zeolite X phase (Faujasite framework). Raw fly ash as well as its derivatives, after being sieved (fractions: ≤ 63, 63–125, 125–180 and ≥ 180 µm), and the obtained zeolite materials were subjected to mineralogical characterisation using powder X-ray diffraction, energy-dispersive X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…The PDI of the particle is 0.210 which proves that the particles are monodispersed in the solvent. and 27.9 °and the peak at 32.6 °could be due to calcite [62].…”
Section: Resultsmentioning
confidence: 96%
“…The PDI of the particle is 0.210 which proves that the particles are monodispersed in the solvent. and 27.9 °and the peak at 32.6 °could be due to calcite [62].…”
Section: Resultsmentioning
confidence: 96%
“…In this case fly ash is mixed with hydroxide solid (pellets) and treated at high temperatures. This method improved modification degree, when spherical, rosetteshaped, or X-shaped crystals can be obtained as consequence of homogeneous and heterogeneous nucleation [52]. The fine fractions of ashes, determining larger reaction surface with NaOH solution, and higher hydroxide quantities, providing more crystallization centers and a new material with nanometric particles, can be obtained.…”
Section: Fusion Methodsmentioning
confidence: 99%
“…• Adsorbents for heavy metal removal [32,33,[43][44][45] • Adsorbents for organic compounds removal [22][23][24]46] • The catalysts [47,49] • Adsorbents for gas retention [50,51] • Zeolites [7,31,46,[52][53][54] • Geopolymers synthesis [55][56][57] • Alkali-activated materials [58] The main applications of fly ashes are presented in Fig. 2.…”
Section: Adsorbents For Pollutant Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Coal is one of the most abundant energy sources worldwide [12]. A previous study reported that the global trend of increasing energy production continued in 2018 [13]. In addition, it is desirable to increase coal-fired power generation by up to 46% of the total electricity production by 2030 [14].…”
Section: Introductionmentioning
confidence: 99%